Manajemen Pembelajaran Daring di Pusat Kegiatan Belajar Masyarakat (PKBM) untuk Meningkatkan Mutu Layanan Pendidikan di Kota Bandung - Purwanti, Harti; Syaodih, Cahya; Karyana, Kakay (Attractive : Innovative Education Journal, 2022)
The change in the learning order from face-to-face to online learning at all levels of education caused by the spread of the Covid-19 virus. The implementation of online learning requires adjustments on the part of teachers, students, and parents. The article was to analyze online learning management at the Community Learning Activity Center (PKBM) to improve the quality of educational services in the city of Bandung. Meanwhile, the specific objectives of this research are to know: (1) Online Learning Planning; (2) Organizing Online Learning; (3) Implementation of Online Learning; (4) Evaluation of Online Learning; (5) Barriers and solutions in the Implementation of Online Learning. Qualitative research approach with descriptive analysis method. The research technique is interview, observation, and document study. The results of the study showed that (1) online learning planning was prepared based on an emergency curriculum adapted to the condition of students who were not yet optimal; (2) Organizing online learning seeks to optimize the role and function of human resources (PKBM) both as leaders, implementers, educators, and external parties, namely students; (3) the implementation of online learning is in accordance with the plan, but the implementation of the learning is still not effective both in delivering material and working on exercises and assignments; (4) The evaluation carried out is not objective in nature and has not been able to reach understanding in the cognitive, affective, and psychomotor domains; (5) Obstacles faced in online learning include human resources for teachers, students and parents, availability of facilities and infrastructure, and cost issues for students who cannot afford, (6) The solutions taken have been able to minimize the obstacles faced but are then faced again on the problems that arise next so that the solutions are not optimal to solve the problems. Keywords: Management Online Learning, Learning at PKBM, Quality of Education Services